Analysis of biomechanical parameters of race walking between trained and untrained among Pantai Running Club - Haikal, Ahmad; Mohamed, Muhamad Noor; Md Radzi, Noor Azila Azreen; Saiful Annur, Muhamad Safiq (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study compares the biomechanical profiles of trained and untrained walkers from the Pantai Runners Club to identify factors influencing race walking efficiency and injury prevention. By analyzing stride length, stride frequency, and joint kinematics of the hip, knee, and ankle, the research highlights how technical adherence to Olympic rules such as maintaining a straight supporting leg differs across skill levels. The findings aim to provide evidence-based insights for optimizing training techniques and improving performance while mitigating the injury risks associated with improper form.